Preparation (Agar Zone Electrophoresis) and Immunological Characterisation of Urokinase - Andrassy, K; Ritz, E (Thrombosis and Haemostasis, 1977)
Urokinase was highly purified by electrophoretical and immunological methods starting with a commercial urokinase preparation (UK-Leo). Contaminating serum proteins and enzyme activities migrated into opposite directions in agar gel electrophoresis which proved to be a valuable preparative method. The final purification achieved was 80,000 Ploug units/mg protein. Traces of albumin, α2 HS-glycoprotein and α2-macroglobulin migrated towards the cathode together with UK in a multimolecular complex. Urokinase antibodies (rabbit) gave with the cathodic fraction 2 precipitation lines (Ouchterlony technique): the one precipitation line corresponded to urokinase (molecular weight on gel chromatography 32,000 daltons), the other corresponded to UK complexed with serum proteins. Urokinase antibodies completely suppressed UK activity in various commercial preparations. All these preparations showed immunological identity; on disc electrophoresis pure urokinase (32,000 daltons, 80,000 Ploug units/mg protein) still gave 2-3 bands suggesting the presence of isoenzymes.This paper is dedicated to Professor G. Schettler on behalf of his 60th birthday